Prevalence of Bronchial Asthma Among Orang Asli in Peninsular Malaysia - Ngui, R.; Lim, Yvonne Ai Lian; Chow, S. C.; de Bruyne, J. A.; Liam, C. K. (Malaysian Medical Association, 2011)
A survey was carried out to determine the prevalence of bronchial asthma and their contributing risk factors among Orang Asli subgroups living in Malaysia using IUATLD questionnaire and spirometry without being discriminatory towards age or gender. Of the 1171 distributed questionnaires, 716 (61.1) comprising of 62.7 Semai Pahang, 51.3 Temiar, 74.2 Mah Meri, 65.6 Semai Perak, 53.6 Temuan, 53.8 Semelai, 61.1 Jakun and 67.4 Orang Kuala subgroups completed their questionnaire and were included in the data analysis. Participants comprised 549 (76.7) children and 167 (23.3) adults, age between 1 to 83 years old, 304 (42.5) males and 412 (57.5) females. The overall prevalence of bronchial asthma was 1.4 of which 1.5 was children, 1.3 adults, 1.0 male and 1.7 female, respectively. Of the 8 subgroups surveyed, 5 out of 10 confirmed asthma cases were Semai Pahang, followed by 3 cases among Mah Meri, and one case each among Temuan and Semai Perak subgroups, respectively. This study also demonstrated that the prevalence of self-reported and confirmed bronchial asthma tend to be higher among those who had close contact with pets, smoking individuals and among those who had a family history of asthma.